2019
DOI: 10.1007/s13670-019-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Update on Interventions to Prevent or Reduce Frailty in Community-Dwelling Older Adults: a Scoping Review and Community Translation

Abstract: Purpose of Review With increasing interest in frailty prevention and management globally, this scoping review provides an update to the current knowledge on interventions to reduce frailty in community-dwelling older adults and its state of translation in real-world settings. Recent Findings Updating previous findings of 14 studies from 2000 to 2016 by Puts et al., we reviewed 10 additional studies from 2016 to 2018 and found that up to date, 18 of 24 studies overall showed effective interventions in preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…There was also very good rapport between the instructors and participants which appeared to improve over the program. The social component [11] and ability of instructors to engage participants during and outside training were important. Since our participants were prefrail/frail older adults, they were at increased risk of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also very good rapport between the instructors and participants which appeared to improve over the program. The social component [11] and ability of instructors to engage participants during and outside training were important. Since our participants were prefrail/frail older adults, they were at increased risk of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Different interventions to reduce frailty have been studied [8][9][10]. Recent reviews highlighted the importance of physical exercise in reducing frailty and improving function in prefrail/frail older adults [11,12]. Economic study also demonstrated that physical exercise is cost-effective in preventing the progression of frailty and disability in older adults living in the community [13].…”
Section: Introductionmentioning
confidence: 99%
“…A strategy to bridge the digital divide of some older people has been to pair them up with others in their family or neighbours who can help with digital access and engagement with the live online training program. While not speci cally measured in our study, the social engagement has been shown to be an important aspect of adherence to group training (8).…”
Section: Discussionmentioning
confidence: 75%
“…Frailty is not a contraindication to exercise but a reason to prescribe it. Frailty can be delayed or reversed through interventions where physical training is a key component, especially during the pre-frail stage (6)(7)(8). There is wide consensus for pre-frail or frail older people to be offered a physical activity program with a progressive, resistance training component (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Different interventions to reduce frailty have been studied (8)(9)(10). Recent reviews highlighted the importance of physical exercise in reducing frailty and improving function in prefrail/frail older adults (11,12). Economic study also demonstrated that physical exercise is cost-effective in preventing the progression of frailty and disability in older adults living in the community (13).…”
Section: Introductionmentioning
confidence: 99%